Success Rate of Zygomatic Implants for Rehabilitation of Severely Atrophied Maxillae: A Review of the Literature (International Journal of Medical and Surgical Sciences, 2016)
Severe resorption in the posterior maxilla sectors as a result of tooth loss along with the process of pneumatization of the maxillary sinus, difficult the prosthetic rehabilitation supported by conventional implants due to the shortage of vertical bone availability. So that over the years they have designed therapeutic alternatives to help overcome these drawbacks. The zygomatic implant was introduced in 1988 by Branemark. This implant has a design which allows it to be positioned over the ridge to the height of the first molar, reducing vestibular cantilever up to 20 % and reducing complications of peri-implant inflammation, infection and gingival hyperplasia, which may lead to perforation horizontal process of the palatine bone. The purpose of this review is to determine the success rate of zygomatic implants for rehabilitation of severely atrophied maxillae. A total of 1410 zygomatic implants and 1673 Traditional implants were included in selected articles. Of these 1410 zygomatic Implants, 365 were conventional loading and 1045 were immediately and early loading, these had a success rate of 98.3 % and 98.7 %, respectively. Of these 1673 Traditional Implants, 463 were conventional loading and 1210 were immediately and early loading, they had a success rate of 93.9 % and 97.8 %, respectively. The overall success rate of zygomatic implants and Conventional implants was 98.6 % and 96.8%, respectively. The rehabilitation of severely atrophied maxilla with fixed prosthesis immediately and conventional loaded by zygomatic implants gives excellent results in the medium term. When comparing traditional treatment modalities, proposals for prosthetic reconstruction of severely atrophied maxilla, the zygomatico implant has the highest success rate over conventional treatments.
Keywords: Zygomatic implants; Success rate; Edentulous maxilla; Resorbed maxilla; Atrophied maxillae